Hybrid nonlinear control strategies for performance enhancement of a doubly-fed induction aero-generator: design and DSP implementation - Bouchaib Rached; Mustapha Elharoussi; Elhassane Abdelmounim (Institute of Advanced Engineering and Science, 2021)
This paper reports on the design and implementation in DSP as hardware in the loop of a nonlinear control strategy for a grid-connected variable speed wind turbine using a doubly fed induction generator (DFIG). The objective of this work is to build a real-time nonlinear hybrid approach combining Backstepping control and sliding mode control strategies for DFIG used in wind energy conversion systems (WECS). The results of the DSP implementation are discussed and qualitative and quantitative performance evaluations are performed under various disturbed conditions. The implementation is performed using the TMS320F28335 DSP combined with the MATLAB/Simulink (2016a) environment. The experimental results have been satisfactorily achieved, which implies that the proposed strategy is an efficient and robust approach to monitor the WECS.